A CRITICAL ANALYSIS OF TEACHING OF INDIAN CLASSICAL MUSIC THROUGH DISTANCE LEARNING SYSTEM IN HIGHER EDUCATION.: उच्च शिक्षा में दूरस्थ शिक्षण प्रणाली के माध्यम से भारतीय शास्त्रीय संगीत का शिक्षणदृएक समीक्षात्मक विश्लेषण - Upadhyay, Dwijesh; Joshi, Nirmala (International Journal of Research -GRANTHAALAYAH, 2017)
The relation of any fine art expresses the elixir of human, physical, and physical world. As civilization grows more and more civilized and cultured, the development of fine arts reaches its peak. Music is a major part of the fine arts. The place of music in Indian civilization is paramount in the fine arts. The great Indian civilization has been underlining the importance of music education since its height. From ancient Vedic and medieval to modern times, the Indian educational system has been concentrating on the education of music; all its parts such as singing, playing and dancing. In the present era, radical changes in the teaching system can be reflected. Divisions like traditional and distance education can also be reflected in the teaching system. Today, the importance of a flexible and alternative system of remote education system cannot be denied. Needless to say that through remote learning, changes in the importance of traditional teaching of music, guruship relations, internal learning method of music and music in life; the importance of all its organs. In the present era, while on the one hand there has been a remarkable change in social and personal life, changes in the teaching method of all subjects can also be targeted. The importance of many new dimensions developed in music education through remote means can be understood. State-of-the-art mediums such as audio, audio, video via Internet, sophisticated equipment of communication, television and radio etc. can be used successfully in music teaching by remote media. The objective of the paper presented is to find a way to solve the problems arising out of it and the benefits of acquiring higher education of Indian classical music through a distance learning system. किसी भी ललित कला का संबंध मानव के दैहिकए दैविक और भौतिक जगत के उत्‍कर्ष को व्‍यक्‍त करता है। सभ्‍यता ज्‍यों.ज्‍यों अधिकाधिक सभ्‍य एवं सुसंस्‍कृत होती जाती है त्‍योंदृत्‍यों ललित कलाओं का विकास अपने चरम पर पहुंचता जाता है। संगीतए ललित कला का एक प्रमुख अंग है। भारतीय सभ्‍यता में संगीत का स्‍थान ललित कला में सर्वोपरि है। महान भारतीय सभ्‍यता अपने उत्‍कर्ष काल से ही संगीत की शिक्षा के महत्व को रेखांकित करती आई है। प्राचीनए वैदिक एवं मध्‍यकाल से आधुनिक काल तक भारतीय शिक्षण प्रणाली संगीत ;उसके सभी अंगों यथा गायनए वादन एवं नृत्‍यद्ध की शिक्षा पर अपना ध्‍यान केन्द्रित करती रही है। वर्तमान युग में शिक्षण प्रणाली में आमूल चूल परिवर्तन को परिलक्षित किया जा सकता है। शिक्षण प्रणाली में पारम्‍परिक एवं दूरस्‍थ शिक्षा जैसे विभाजनों को भी परि‍लक्षित किया जा सकता है। आज दूरस्‍थ शिक्षा प्रणाली की लचीली तथा वैकल्पिक व्‍यवस्‍था के महत्‍व को नकारा नहीं जा सकता। कहना न होगा कि दूरस्‍थ शिक्षण माध्‍यम से संगीत की पारम्‍परिक शिक्षाए गुरूदृशिष्‍य संबंधोंए संगीत की आंतरिक शिक्षण पद्धति तथा जीवन में संगीत;उसके सभी अंगोंद्ध के महत्‍व में आए बदलावों को अनुभव किया जा सकता है। वर्तमान युग में जहां एक ओर सामाजिक एवं व्‍यक्तिगत जीवन में आश्‍चर्यजनक परिवर्तन आया है वहीं सभी विषयों की शिक्षण पद्धति में भी परिवर्तन को लक्षित किया जा सकता है। दूरस्‍थ माध्‍यम से संगीत शिक्षा में विकसित कई नए आयामों का महत्‍व समझा जा सकता है। तकनीकी के अत्‍याधुनिक माध्‍यमों दृ जैसे ऑडियोदृविडियो माध्‍यमए इंटरनेटए संचार के अत्‍याधुनिक उपकरणए टेलीविजन एवं रेडियो आदि का उपयोग दूरस्‍थ माध्‍यम द्वारा संगीत शिक्षण में सफलतापूर्वक किया जा सकता है । प्रस्‍तुत शोधपत्र का उद्देश्‍य दूरस्‍थ शिक्षण प्रणाली के माध्‍यम से भारतीय शास्‍त्रीय संगीत की उच्‍च शिक्षा ग्रहण करने के लाभए इससे उत्‍पन्‍न समस्‍याओं एवं उनके निराकरण का मार्ग खोजना है ।